DOI: 10.29007/848q
|View full text |Cite
|
Sign up to set email alerts
|

Adopting and Implementing a Government Cloud in Saudi Arabia, an Integral Part of Vision 2030

Abstract: Cloud computing is a relatively mature and robust technology that has promised its users with several proven advantages, such as cost reduction, immediate scalability, and resource sharing. The Cloud is built based on providing resources as services, such as providing Infrastructure, Platform, and Software as a Service. Such approach enables Cloud users to access these services based on their demand. In the government sector of Saudi Arabia, adoption and utilization of the Cloud is minimal. Despite being adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…There is a necessity for global governments to invest in cybersecurity infrastructure and systems to enhance the manner in which they provide diverse services to their citizens [13]. The creation of robust e-government systems is also critical for the maintenance of a steady progression toward technological advancements in line with other global powers [14]. Cyber threats pose significant risks to the implementation of e-government systems.…”
Section: Problem Evolutionmentioning
confidence: 99%
“…There is a necessity for global governments to invest in cybersecurity infrastructure and systems to enhance the manner in which they provide diverse services to their citizens [13]. The creation of robust e-government systems is also critical for the maintenance of a steady progression toward technological advancements in line with other global powers [14]. Cyber threats pose significant risks to the implementation of e-government systems.…”
Section: Problem Evolutionmentioning
confidence: 99%
“…In 2019, the same authors in [16] presented the previous proposal in detail and considered all parties contributing to developing and protecting this system. They proposed to create an Intelligent Government Cloud (IGC) powered by the National Center.…”
Section: Recommendationsmentioning
confidence: 99%
“…Several studies investigated challenges facing CC adoption, emphasizing the security challenges and ensuring that it is one of the significant factors challenging CC in different sectors [15]- [23]. Such as [23] investigated the adoption within the governmental sector in Saudi Arabia and found that security, single point of failure, and privacy as challenges concerning the proper implementation of cloud computing. Thus, the study proposed a structure for the appropriate adoption and implementation of cloud solutions.…”
Section: Introductionmentioning
confidence: 99%